EFEKTIVITAS MODEL STAD BERBASIS PANCASILA DALAM PEMBENTUKAN KARAKTER DISIPLIN - Hani Nuraeni Hani; Sri Rahayu Pudjiastuti; Mohamad Sutisna (Perkumpulan Peneliti dan Pegiat Literasi, 2026)
This study addresses the limited use of contextual and participatory learning models in Islamic boarding schools for fostering students’ disciplinary character. In many pesantren, discipline is still shaped mainly through rules and sanctions, while learning activities have not been systematically designed to internalize Pancasila values and build intrinsic awareness. This study aimed to develop and test the effectiveness of a Student Teams Achievement Division (STAD) learning model based on Pancasila values for strengthening the disciplinary character of santri at Pondok Pesantren Ar-Rahmaniyyah Sukabumi. The study employed a research and development design consisting of preliminary study, product design, expert validation, limited trial, revision, and field testing. Data were collected through observation, interviews, questionnaires, and pretest-posttest instruments. The findings show that the developed module was categorized as very valid, practical, and effective. Expert validation reached a mean score of 4.3, while students’ responses indicated high practicality. The average score increased from 63.44 in the pretest to 80.31 in the posttest. The model was more effective in strengthening disciplinary awareness than in changing rule-compliance behavior, which requires longer habituation. These findings suggest that integrating STAD, Pancasila values, and pesantren discipline can provide a practical model for character education in Islamic boarding schools.